2019
DOI: 10.1186/s40842-018-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of immune checkpoint inhibitors-induced endocrinopathies in cancer patients: a scoping review of case reports

Abstract: BackgroundSince 2011 six immune checkpoint inhibitors (ICI) have been approved to treat patients with many advanced solid tumor and hematological malignancies to improve their prognosis. Case reports of their endocrine immune-related adverse events [irAEs]) are increasingly published as more real-world patients with these malignancies are treated with these drugs. They alert physicians of a drug’s AEs (which may change during a drug’s life cycle) and contribute to post-marketing safety surveillance. Using a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(171 citation statements)
references
References 168 publications
5
164
0
2
Order By: Relevance
“…Notably, few case reports for this event have been published in clinical trials, but hypopituitarism seemed higher in the spectrum of ICI-induced endocrinopathies in cancer patients based on the scoping review of case reports. 8 Our study has some limitations. First, because of the heterogeneity of the included studies, an assessment of additional potential risk factors, including the role of sex, age, and baseline pituitary-adrenal function, is needed.…”
Section: F I G U R E 2 Risk Of Serious-grade Adrenal Insufficiency Inmentioning
confidence: 89%
See 1 more Smart Citation
“…Notably, few case reports for this event have been published in clinical trials, but hypopituitarism seemed higher in the spectrum of ICI-induced endocrinopathies in cancer patients based on the scoping review of case reports. 8 Our study has some limitations. First, because of the heterogeneity of the included studies, an assessment of additional potential risk factors, including the role of sex, age, and baseline pituitary-adrenal function, is needed.…”
Section: F I G U R E 2 Risk Of Serious-grade Adrenal Insufficiency Inmentioning
confidence: 89%
“…However, the risk of hypopituitarism was significantly higher in patients treated with ICI regimens than in those in the control group. Notably, few case reports for this event have been published in clinical trials, but hypopituitarism seemed higher in the spectrum of ICI‐induced endocrinopathies in cancer patients based on the scoping review of case reports …”
Section: Discussionmentioning
confidence: 99%
“…Endocrinopathies affecting the pituitary and thyroid glands are emerging as some of the most common adverse events associated with immunotherapy and often the most symptomatic among these ICI‐related endocrinopathies (irEs) . Meanwhile, apart from hypophysitis and thyroid dysfunction, insulin‐deficient diabetes mellitus and primary adrenal insufficiency have recently been reported as less frequent irEs due to ICI therapy and even more rarely hypoparathyroidism, however, all of them can be life‐threatening if not promptly recognized and treated . Several observational studies and case series have reported that hypophysitis is mainly associated with anti‐CTLA4 therapy and thyroid dysfunction with anti‐PD1 therapy …”
Section: Introductionmentioning
confidence: 99%
“…4 Meanwhile, apart from hypophysitis and thyroid dysfunction, insulin-deficient diabetes mellitus and primary adrenal insufficiency have recently been reported as less frequent irEs due to ICI therapy and even more rarely hypoparathyroidism, however, all of them can be life-threatening if not promptly recognized and treated. 5,6 Several observational studies and case series have reported that hypophysitis is mainly associated with anti-CTLA4 therapy and thyroid dysfunction with anti-PD1 therapy. 3 The precise mechanisms of action underlying these endocrine irEs remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review yielded 25 articles documenting irAE incidence, management guidelines, toxicity profiles, and associated symptomatology [4,9,[11][12][13][14][15][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] . From these, we identified 75 possible inflammatory reactions/immune conditions across 11 organ systems, ranging from very common to rare.…”
Section: Literature Reviewmentioning
confidence: 99%